Ecologically Conscious Consumer and Consumption Behavior - El-Kassar, Abdul-Nasser (2014)
Environmental concerns and involvement in environmental matters became more noticeable during the 2000's. Academicians and researchers have been investigating and determining factors and criteria that characterize the ecologically conscious consumers. Today, business entities and organizations are not only responsible for maintaining effective wastes' disposal to reduce pollution, they rather became further involved in developing, manufacturing and marketing new products that are based on the utilization of eco-friendly alternatives, starting from the composition and blueprint of the package, reaching the product itself. There are significant challenges associated with examining the topic (ECCCB); our primary objective is to address these challenges. As a context for our study, we have chosen the survey method to collect data using a self-administered questionnaire, a sample of 250 students from four major Lebanese universities. The sample is from a diverse socioeconomic group of young people and represents a relatively unexplored, yet extremely important, consumer market segment. A key finding showed that social influence was a predictor of Lebanon students' green purchasing behavior and consumption followed by environmental concern, environmental protection and perceived environmental responsibility